STYLISTIC FEATURES OF DEGREES OF ADJECTIVES IN LITERARY TEXTS - Odilova Sevaraxon Tulqinovna (International Journal of Literature and Language Studies, 2026)
This article examines the grammatical-semantic and stylistic features of degrees of adjectives manifested in Uzbek literary texts. It analyzes the functional potential of degrees of adjectives in literary discourse, particularly the role of positive, comparative, superlative, and attenuative degree forms in creating imagery, intensifying or weakening a particular quality, expressing the psychological and emotional states of characters, and conveying the author’s subjective evaluation. Particular attention is also paid to the linguopoetic potential of degrees of adjectives in enhancing the emotional expressiveness and aesthetic impact of literary texts. The study employs descriptive, contextual, semantic-stylistic, and linguopoetic methods of analysis. Based on the findings, it is substantiated that degrees of adjectives function not only as a grammatical category but also as an important stylistic and linguopoetic device in literary texts.